Which way of design programming activities is more effective to promote K‐12 students' computational thinking skills? A meta‐analysis - Sun, Lihui; Hu, Linlin; Zhou, Danhua (Journal of computer assisted learning, 2021)
Promoting the cultivation of computational thinking (CT) skills in programming activities has become a key issue in the K‐12 curriculum, however, there is no unified conclusion on how to design programming activities to promote the acquisition of CT skills more effectively. The purpose of this study is to determine the effectiveness of using programming to enhance K‐12 students' CT skills and explore the influence of various programming instructional design factors on the acquisition of CT skills. This study presents a quantitative meta‐analysis. A systematic search of randomized controlled studies on the influence of programming on CT skills. A total of 86 empirical studies with 114 effect sizes met the study selection criterion. The results showed that programming improved K‐12 students' CT skills in general (Hedges' g = 0.601, 95% CI [0.505, 0.697], p < 0.001). No publication bias was detected. Besides, we found that the interdisciplinary integration of programming, the duration of programming intervention within 1 week to 1 month, the class size of less than 50 students, and a reasonable selection of programming instruments and CT assessment types may be more conducive to promoting students' CT skills. Based on these findings, we suggest that programming instructional design should be planned reasonably to make the best use of technology towards developing students' CT skills. This will be of great significance to programming teaching and CT education in K‐12. Lay Description What is already known about this topic The cultivation of computational thinking (CT) in K‐12 has become a key issue. One of the latest trends in the education field is computer programming in K‐12 classrooms to cultivate students' CT skills. Programming teaching design may affect the influence of programming education on students' CT skills. However, there is a lack of overall quantitative synthesis of existing empirical research. What this paper adds A meta‐analysis of 86 studies was conducted to provide systematic evidence that programming education is effective to promote K‐12 students' CT skills. Programming teaching design factors such as subjects, intervention duration, sample size, programming instruments and assessment types can affect CT skills in programming activities. Programming activity forms cannot affect CT skills in programming activities. Implications for practice and/or policy The implementation of programming education in K‐12 schooling can effectively cultivate students' CT skills. Programming teaching design should be planned reasonably to make the best use of technology towards developing students' CT skills. The interdisciplinary integration of programming, the duration of programming intervention within one week to one month, control of class size to less than 50 students, and a reasonable selection of programming instruments and assessment types may be more conducive to promoting students' CT skills.